Palliative Therapy of Esophageal Stent Installation with Shim Modified Fixation Techniques on An Esophageal Adenocarsinoma Patients - Yudith Annisa Ayu Rezkita (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Esophageal carcinoma is a progeny disease that often results in significant disruption to the ability to ingest solid foods and liquid foods at an advanced stage. Reported case of a 27-year-old man with a diagnosis of an intestinal type of adenocarcinoma gastroesophageal junction stage III with a dysphagia score 4. Diagnosis based on anamnesis, endoscopy and anatomical pathology. Patients have undergone chemotherapy and palliative therapy with esophageal dilatation. Patients experienced improvement in dysphagia score from initial score 3 (unable to swallow solid or liquid food), to 2 (able to swallow semisolid food) after the installation of esophageal stent. The patient planned to continue therapy his chemotherapy.